Formulasi Crude Palm Oil dan Palm Kernel Oil Terhadap Kualitas Sabun Mandi Padat - Rani; Sikmenes, Alfadina Omega; Fajarwati, Yuni Eka; Widyastuti, Fikka Kartika (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2023)
Crude Palm Oil (CPO) has quite large potential for the cosmetic and pharmaceutical industries. CPO contains carotenoids, tocopherols and tocotrienols which function as natural antioxidants. Soap containing carotenoids is good for the skin. Palm Kernel Oil (PKO) is a substitute for goat's milk, where goat's milk and PKO both have natural antibacterial properties. To obtain good bath soap, research was carried out on solid bath soap from CPO and PKO. The research method is an experimental method with the main reaction, namely saponification. The saponification reaction is a reaction to form soap, which is usually made from fats and bases. To determine the CPO and PKO formulations on the characteristics of solid bath soap with NaOH concentrations of 20%, 25%, 30% respectively, with a stirring time of 30 minutes and a stirring temperature of 70oC. Next, tests were carried out with several parameters, namely analysis of water content, pH, foam power, emulsion and free alkali. After analyzing and comparing soap with the main ingredients of crude palm oil and palm kernel oil, soap with a NaOH concentration of 25% is suitable for use because it meets SNI with a water content value of 11.34%, pH 10.5, free alkali 0.1%, foam height 12 .5 cm, and foam power of 90.4%. Abstrak Crude Palm Oil (CPO) atau minyak sawit mentah mempunyai potensi relatif besar untuk industri kosmetik dan farmasi. CPO mengandung karotenoid, tokoferol, dan tokotrienol yang berperan sebagai antioksidan alami. Palm Kernel Oil (PKO) merupakan sebagai pengganti susu kambing, diaman susu kambing dan PKO sama- sama memiliki sifat antibakteri alami. Untuk memperoleh sabun mandi yang baik maka dilakukan penelitian sabun mandi padat dari CPO dan PKO. Metode penelitian adalah metode eksperimen dengan reaksi utama yaitu saponifikasi atau reaksi pembentukan sabun. Untuk mengetahui formulasi CPO dan PKO terhadap karakteristik sabun mandi padat dengan konsentrasi NaOH masing- masing 20%, 25%, 30%, dengan waktu pengadukan 30 menit serta suhu pengadukan 70oC. Selanjutnya dilakukan pengujian dengan beberapa parameter yaitu analisa kadar air, pH, daya busa, emulsi, dan alkali bebas. Setelah dilakukan dianalisa dan perbandingan sabun dengan bahan utama crude palm oil dan palm kernel oil, sabun dengan konsentrasi NaOH 25% layak digunakan karena memenuhi SNI dengan nilai kadar air 11,34%, pH 10.5, alkali bebas 0,1%, tinggi busa 12,5 cm, serta daya busa 90,4%.